2016
DOI: 10.1128/cvi.00091-16
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Assembling Detoxified Staphylococcus aureus Alpha-Hemolysin Mimicking the Wild-Type Cytolytic Toxin

Abstract: Staphylococcus aureus alpha-hemolysin (Hla) assembles into heptameric pores on the host cell membrane, causing lysis, apoptosis, and junction disruption. Herein, we present the design of a newly engineered S. aureus alpha-toxin, HlaPSGS, which lacks the predicted membrane-spanning stem domain. This protein is able to form heptamers in aqueous solution in the absence of lipophilic substrata, and its structure, obtained by transmission electron microscopy and single-particle reconstruction analysis, resembles th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Equal molar concentrations of recombinant LukS-PV tag-free (code: 0540-001, IBT Bioservices) and recombinant LukF-PV tag-free (code: 0540-002, IBT Bioservices) were premixed to generate a working concentration of PVL. α-toxin (Hla) and its detoxified mutant Hla H35L were produced as previously described ( 20 ). Lipopolysaccharide contamination in purified proteins was assessed using the LAL test (from Charles River).…”
Section: Methodsmentioning
confidence: 99%
“…Equal molar concentrations of recombinant LukS-PV tag-free (code: 0540-001, IBT Bioservices) and recombinant LukF-PV tag-free (code: 0540-002, IBT Bioservices) were premixed to generate a working concentration of PVL. α-toxin (Hla) and its detoxified mutant Hla H35L were produced as previously described ( 20 ). Lipopolysaccharide contamination in purified proteins was assessed using the LAL test (from Charles River).…”
Section: Methodsmentioning
confidence: 99%
“…The sequence encoding the signal peptide (residues 1-26) of Hla was removed. The sequence encoding the two b sheets involved in forming the heptameric pore was replaced by a sequence encoding "PSGS", as reported previously (18). Then, the two sequences were linked together by a "GGGGS" linker, with sequences encoding an Nterminal TPA signal peptide and a C-terminal 8×His tag.…”
Section: Dna Manipulationmentioning
confidence: 99%
“…a-Hemolysin (Hla) is a pore-forming toxin secreted by Staphylococcus aureus that can self-assemble into a heptameric pore structure on host cell membranes, resulting in cell lysis and death (17). A previous study revealed that an Hla mutant (mHla) lacking the two b-sheets that form the pore-like structure retains the ability to assemble into a heptamer but loses its biological activity (18). We have demonstrated that mHla could serve as a carrier protein to aid the assembly of IC43, a candidate antigen of Pseudomonas aeruginosa (19), resulting in improved immunogenicity and protective efficacy of the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Several Hla vaccines have been tested in preclinical animal models including (i) a full length nontoxigenic Hla (Hla H35L ), (ii) the N-terminal 50 amino acids of Hla fused to glutathione S-transferase (GST) (GST-Hla 1-50 ), (iii) a structurally designed vaccine consisting of 62 non-contiguous Hla amino acids, and (iv) Hla engineered to lack the predicted membrane-spanning stem domain (HlaPSGS) [ 10 , 12 , 13 , 14 ]. Despite some successes in animal models, no S. aureus or Hla vaccine has been successful in clinical trials.…”
Section: Introductionmentioning
confidence: 99%